The Effect of Child Sexual Abuse Prevention Song Among Elementary School Children:Pilot Study - Solehati, Tetti; Hermayanti, Yanti; Kosasih, Cecep Eli; Mediani, Henny Suzana (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Child Sexual Abuse (CSA) becomes a problem in the world that is quite large and has adverse effects, both short and long term. The prevalence continues to increase every year. Generally, elementary school-age likes to sing a song. Meanwhile, school-age is the time to study. A song is expected to increase knowledge of skills in preventing sexual violence. The objective of this study to assess the effect of education through songs on the level of skill knowledge about preventing CSA in school-age children. The type of research was quasi-experiment with one group pre and post-test design. The sample size used a total sampling that all students became the sample. The study involved 323 students in grades 4-6 at SDN Dayeuhkolot, Bandung Regency. The treatment was an education on prevention of the CSA on school-age children, it was given using the jargon "TANGKIS" with the method of giving songs through a video about the prevention of sexual violence against children. The instrument was adopted from the Aprilaz design (2016) which was modified by Suhenda (2019). Data analysis using univariate analysis with frequency and percentage distribution, and bivariate analysis using t-test. The study showed that 289 students (89.5%) were able to have good knowledge about the prevention of CSA before the intervention and after the intervention increased to 319 (98.8%) (p= 0.001). Education through songs influences students' knowledge regarding the prevention of CSA. Suggestion: this research is to be able to make education programs to prevent CSA of school-age children regularly and explore other educational methods that can effectively influence the improvement of knowledge, attitudes, and skills in protecting themselves from the threat of CSA.Abstrak: Child Sexual Abuse (CSA) menjadi masalah di dunia yang cukup besar dan berdampak buruk, baik jangka pendek maupun jangka panjang. Prevalensinya terus meningkat setiap tahunnya. Umumnya, anak usia sekolah dasar suka menyanyikan sebuah lagu. Sedangkan usia sekolah adalah masa menuntut ilmu. Sebuah lagu diharapkan dapat meningkatkan pengetahuan keterampilan dalam mencegah kekerasan seksual. Tujuan penelitian ini untuk mengkaji pengaruh pendidikan melalui lagu terhadap tingkat pengetahuan keterampilan tentang pencegahan CSA pada anak usia sekolah. Jenis penelitian adalah eksperimen semu dengan rancangan one group pre and post test. Besar sampel menggunakan total sampling yaitu semua siswa menjadi sampel. Penelitian ini melibatkan 323 siswa kelas 4-6 di SDN Dayeuhkolot, Kabupaten Bandung. Perlakuan tersebut berupa edukasi pencegahan PSK pada anak usia sekolah, diberikan dengan menggunakan jargon “TANGKIS” dengan metode pemberian lagu melalui video tentang pencegahan kekerasan seksual terhadap anak. Instrumen diadopsi dari desain Aprilaz (2016) yang dimodifikasi oleh Suhenda (2019). Analisis data menggunakan analisis univariat dengan distribusi frekuensi dan persentase, dan analisis bivariat menggunakan uji-t. Hasil penelitian menunjukkan bahwa 289 siswa (89,5%) mampu memiliki pengetahuan yang baik tentang pencegahan CSA sebelum intervensi dan setelah intervensi meningkat menjadi 319 (98,8%) (p = 0,001). Edukasi melalui lagu mempengaruhi pengetahuan siswa tentang pencegahan CSA. Saran: penelitian ini agar mampu membuat program edukasi pencegahan CSA anak usia sekolah secara rutin dan mendalami metode pendidikan lain yang secara efektif dapat mempengaruhi peningkatan pengetahuan, sikap, dan keterampilan dalam melindungi diri dari ancaman CSA.